1986
DOI: 10.1111/j.1365-2222.1986.tb00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketotifen in pollen‐induced asthma: a double blind placebo‐controlled study

Abstract: Twenty-nine children with an average age of 105 years were studied with respect to the protective effect of ketotifen on pollen-induced bronchial asthma. All of them were sensitive to deciduous tree pollen, the diagnosis being verified by bronchial challenge. The children were stratified in matched pairs and randomly allocated to two treatment groups, placebo or ketotifen 1 mg twice daily. The study was double-blind and was performed during the whole of the deciduous tree pollen season. Daily pollen counts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Similar results were seen in terms of the effect of ketotifen on nasal discharge (8). Other studies demonstrated positive effects by ketotifen in older children (9, 10). A reduction in the subsequent prevalence of asthma was seen in infants with atopic dermatitis (11) and in infants with a history of allergy and raised serum total IgE (12).…”
mentioning
confidence: 90%
“…Similar results were seen in terms of the effect of ketotifen on nasal discharge (8). Other studies demonstrated positive effects by ketotifen in older children (9, 10). A reduction in the subsequent prevalence of asthma was seen in infants with atopic dermatitis (11) and in infants with a history of allergy and raised serum total IgE (12).…”
mentioning
confidence: 90%
“…Effects of ketotifen, a first generation H 1 ‐specific receptor antagonist, seemed to be promising because of possible intrinsic anti‐inflammatory properties resulting in reduction of eosinophilic activation and migration, and normalization of β‐receptor expression thus preventing tachyphylaxis [ 130, 131]. Since then, many double‐blind, placebo‐controlled studies estimating clinical efficacy of ketotifen in asthma have been performed [ 131–151]. Overall, ketotifen (1 mg bid) seems to ameliorate asthma severity slightly (especially in children), with improvement of symptoms, rescue medication use and number of exacerbations.…”
Section: Other Drugs With Anti‐inflammatory Propertiesmentioning
confidence: 99%
“…Ketotifen fumarate shares properties with the two latter groups of compounds (12). Clinical studies have shown ketotifen to be effective in the treatment of asthma (13, 14) and AC (15, 16). It exerts anti‐anaphylactic and antihistamine activities, mainly through inhibition of the release of chemical mediators such as histamine and leukotrienes (LT) from sensitized mast cells (17, 18).…”
mentioning
confidence: 99%